Preparo e autoadministração de insulina entre usuários com diabetes mellitus - Santos, Wallison Pereira dos (2020)
Introduction: Insulin therapy is one of the treatment modalities for controlling Diabetes Mellitus (DM) that requires understanding, adherence and skill in the preparation and self-administration technique, in order to avoid and / or delay local complications related to the procedure and, consequently, to the glycemic control. Objective: to analyze the practice of preparing and administering insulin among users with DM, as recommended by the Brazilian Diabetes Society. Method: This is a descriptive, cross-sectional study with a quantitative approach, carried out in an endocrinology outpatient clinic at a University Hospital in the capital of the state of Paraíba. 136 individuals taking insulin participated in the study. For data collection, two instruments were used, a form with sociodemographic and clinical aspects and a script for observing the simulated practice. The study was developed in three stages: application of the form; clinical examination of the locations of insulin application and, finally, the simulated practice, in which users performed the technique commonly used, using a prototype built for this purpose. The study was approved by the Research Ethics Committee of Hospital Universitário Lauro Wanderley, under opinion No. 3.457.517 and CAAE: 16560819.4.0000.5183. The data were tabulated in electronic spreadsheets and converted to the statistical program R, the following analyzes were performed: Descriptive, Chi-square and logistic regression. Results: Among the participants, 50% were 51-70 years old, 74.26% were female, 58.09% were married / in a stable relationship, 36.77% had between 9 and 11 years of study, 82.35% they did not rotate the application sites, 68.38% reused syringes and needles and 42% had hematoma and lipodystrophy as the main complication. Regarding the technique of insulin preparation and self-administration, it was observed that users had flaws, especially in the insulin preparation stage. Regarding the variables predicting tissue complications in the logistic regression model, the fact that the patient was not rotated and was single, widowed or divorced was statistically significant, with the outcome of tissue complications. Conclusion: Users have limitations for the performance of the insulin preparation and self-administration technique, and health professionals involved in the care of this population are responsible for the intervention focused on these weaknesses, in order to favor adherence to treatment in an appropriate manner, thus reducing the occurrence complications.